Aggressive Mandibular Squamous Cell Carcinoma Mimicking Periodontal Disease in a Non‐Transplanted Patient With Fanconi Anemia - Cassius Carvalho Torres‐Pereira; Laura Grein Cavalcanti; Marta Aparecida Alberton Nuernberg; Juliana Lucena Schussel; José Miguel Amenábar Céspedes (Head & Neck, 2026)
ABSTRACT Background Fanconi anemia (FA) is associated with markedly increased risk for early‐onset oral squamous cell carcinoma (OSCC). Methods We report an aggressive mandibular squamous cell carcinoma in a 26‐year‐old non‐transplanted woman with FA initially interpreted as localized periodontal disease adjacent to a tongue leukoplakia. Results Initial examination demonstrated mild gingival inflammation and localized alveolar bone loss involving the right mandibular molars. Forty‐five days later, the patient returned with facial asymmetry, severe bone destruction, and grade III tooth mobility. Cone beam computed tomography revealed extensive mandibular osteolysis, and biopsy confirmed squamous cell carcinoma with extensive intraosseous involvement. Despite surgical treatment, the patient died 3 months later. Conclusions This case highlights the potential limitations of surveillance strategies focused predominantly on visible mucosal lesions and reinforces that rapidly progressive periodontal‐like destruction in patients with FA should raise immediate suspicion for malignancy.